Transanal endoscopic microsurgical submucosal dissection: an efficient treatment option for giant superficial neoplastic lesions of the rectum - Kouladouros, Konstantinos; Baral, Jörg (Visceral medicine, 2022)
Introduction: The resection of giant superficial neoplastic lesions of the rectum (>5 cm) is challenging even for experienced specialists. Endoscopic mucosal resection, endoscopic submucosal dissection (ESD), and transanal endoscopic microsurgery (TEM) have all been used for the treatment of such tumors. However, because of their individual disadvantages, the ideal technique for the treatment of these lesions has yet to be determined. Transanal endoscopic microsurgical submucosal dissection (TEM-ESD) is a recently developed hybrid technique that combines the advantages of conventional TEM and flexible ESD. The aim of our study was to assess the feasibility and outcomes of TEM-ESD for the resection of giant superficial rectal neoplasms. Methods: We retrospectively analyzed all cases of TEM-ESD performed in the Department of Surgery of the Municipal Hospital of Karlsruhe between 2010 and 2020 and isolated 43 patients with superficial rectal lesions >5 cm according to the postoperative histology report. The diagnostic, perioperative, histological, and follow-up data of the patients were analyzed in the form of a retrospective, observational cohort study. Results: We identified 43 cases matching our criteria, including 35 adenomas and 8 occult adenocarcinomas. The median size of the lesions was 75 mm and the median operating time was 81.5 min. En bloc resection was possible in all cases, and histologically complete en bloc resection was confirmed in 29 cases. Five patients presented with postoperative bleeding, 2 of which were treated conservatively, 2 were treated endoscopically, and 1 required revision surgery. The median follow-up period was 15 months. There was no recurrence among patients with adenomas, 1 recurrence of a low-risk carcinoma, and 1 recurrence after the resection of a high-risk carcinoma in a patient that refused further treatment. During the follow-up period, 3 patients developed a stenosis, which was treated endoscopically. Conclusions: TEM-ESD is a feasible and safe therapeutic option for the treatment of giant superficial rectal neoplasms.